Physical performance and positional differences among young female volleyball players - Paz, G. A.; Gabbett, T. J.; Maia, M. F.; Santana, H.; Miranda, H.; Lima, V. (The Journal of Sports Medicine and Physical Fitness, 2017)
BACKGROUND: The purpose of this study was to investigate the association among anthropometric, physical performance parameters, and dynamic postural control attributes of young female volleyball athletes, and to determine if differences exist in these attributes according to playing position.